Spread IT Ent.: matcha hazelnut spread / Nurelyana Abdul Rashid ... [et al.] - Abdul Rashid, Nurelyan; Zuhairah, Nurhanis; Yusni, Muhammad Nuhairy; Zainal Effendy, Muhammad Syarifuddin Imran (2023)
Everybody who likes green tea may get a premium food flavoring from Spread IT Ent. When people desire something sweet, our organization offers a very nice spread in terms of flavor. This spread will bring a typical person and a vegetarian together because their tastes in food are different. Since some vegans eat matcha spread only sometimes, our firm strives to be the top food producer in order to enhance the lives of our vegans and provide them with new experiences by supplying plant-based matcha spread. Our goal in developing this matcha spread is to become the largest matcha supplier on the world market. Due to our continued business expansion, we believe that in the future our company will rank among the largest food manufacturers both locally and globally. The headquarters of Spread IT Ent. is located in Telok Mengkuang Panglima Garang, Selangor, and the company was registered under the Business Act of 1956 and with Suruhanjaya Syarikat Malaysia (SSM). The collaboration of four experts from various fields owns the business. These 4 people will actively participate in the company's management. This knowledge has been gathered by Spread IT to offer managerial knowledge. For three years, Spread IT has worked with the food industry. Everyone who enjoys food, whether they are vegan or not, as well as those who lead healthy lifestyles, make up our clientele. In addition to satisfying vegan flavour, our product is manufactured with nutritious components to support our customers' healthy lifestyles. Because our product contains high-quality, natural sweeteners, natural nutrients, and palm oil products, it is comprised of healthy components. It is suitable for everyone because it has such a large positive influence on our customer. In reality, Malaysia is listed as one of the unhealthy countries with inadequate health awareness on the New Straits Time website as of November 11, 2021. Additionally, when our Health Minister Khairy Jamaludin was being interviewed by a television network. He claims that "In Malaysia, one in two individuals including myself are obese and overweight, while one in four people don't engage in any form of physical exercise and one in twenty people follow a healthy eating regimen." Our nation clearly has a poor level of healthy living, and we need to prevent this in the future. We thus use this chance to promote our goods for a better future.